P98 Investigation of unilateral pleural effusion: what CT scan should be ordered?. (12th November 2019) - Syer, TJ; Arnold, D; Edey, A; Maskell, N
Abstract : Background: The BTS pleural disease guidelines recommend all patients with an undiagnosed unilateral pleural undergo computed tomography (CT) of the thorax with contrast. 1 However, there is no consensus on whether to include the abdomen and pelvis in the initial examination, with the BTS mesothelioma guidelines recommending this as an area that requires further research. 2 Methods: We performed a cross-sectional study using prospectively collected data between March 2008 and September 2018 of patients presenting with an undiagnosed pleural effusion. All patients consented for this study, underwent CT thorax, abdomen and pelvis as part of their standard work up and were followed for 12 months or until death, to ensure a robust diagnosis. Results: 249 patients were included; mean age 72 (IQR 66–80), 167 (67%) male, WHO PS 0–1 (62%), 2–3 (37%), 190 (76%) out-patients, 147 (59%) right sided, 87 (35%) previous asbestos exposure. The final diagnosis was malignancy in 159 (64%). The CT thorax alone was consistent with the final diagnosis in 171 (69%). There were clinically significant findings below the costophrenic recesses in 59 patients (23.6%). Including the abdomen increased the diagnostic yield of clinically significant findings by 11.6% (n=29). Within the malignant group additional findings were of a primary tumour (6), upstaging of disease (19) and alternative biopsy sites (2). Including the pelvis resulted in 30 additional findings (12%), primary tumours (11), upstaging of disease (13) and alternative biopsy sites (3). 14 (5.6%) had an underlying ovarian cancer – 86% would have been missed if only CT chest and abdomen was performed. In females the pelvic CT revealed additional findings in 18 (22%). Conclusion: CT thorax, abdomen and pelvis has a considerably higher diagnostic yield than more limited sequences in the work up of unilateral pleural effusions and this paper lends support to its inclusion for standard of care.